2020
DOI: 10.1093/nar/gkaa163
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omic analysis of gametogenesis reveals a novel signature at the promoters and distal enhancers of active genes

Abstract: Epigenetic regulation of gene expression is tightly controlled by the dynamic modification of histones by chemical groups, the diversity of which has largely expanded over the past decade with the discovery of lysine acylations, catalyzed from acyl-coenzymes A. We investigated the dynamics of lysine acetylation and crotonylation on histones H3 and H4 during mouse spermatogenesis. Lysine crotonylation appeared to be of significant abundance compared to acetylation, particularly on Lys27 of histone H3 (H3K27cr) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 111 publications
0
29
0
Order By: Relevance
“…Genome-wide associations between histone Kcr and gene expression have been studied in various organisms [4,9,12,14,[26][27][28], which indicate that it may act as a transcription activating histone PTMs. By contrast, histone Kla is only been reported to implicate in inflammation and oncogenesis-related transcription programs [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide associations between histone Kcr and gene expression have been studied in various organisms [4,9,12,14,[26][27][28], which indicate that it may act as a transcription activating histone PTMs. By contrast, histone Kla is only been reported to implicate in inflammation and oncogenesis-related transcription programs [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study exploring histone lysine crotonylation in the context of mouse spermatogenesis, we have shown that H3K27 is modified by this acylation at a similar level to acetylation in the latest stages of the differentiation process. More precisely, H3K27cr was detected in combination with either H3K36unmod or H3K36me2 [ 10 ]. In that work, we did not optimize MS analysis conditions to produce the diagnostic/immonium ions of Kcr; of note, its structure containing an unsaturation dramatically reduces possibilities of isobaric PTM combinations.…”
Section: Resultsmentioning
confidence: 99%
“…Further acylations were successively discovered including crotonylation [ 5 ], hydroxybutyrylations [ 6 , 7 ], benzoylation [ 8 ] and lactylation [ 9 ]. Of note, even though these histone PTMs remained “ignored” for decades, it appears that their relative stoichiometry to acetylation is far from negligible on certain lysine residues and in given cellular contexts [ 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SOX30 protein (SRY-box containing gene 30), the only member of group H, has been characterized briefly only in a few species so far. SOX30 has been isolated from mice, humans and Nile tilapis, and it has been connected with mammalian spermatogonial differentiation and spermatogenesis [69][70][71][72]. Recently, it has been demonstrated that the SOX30 protein could be a novel epigenetic silenced tumor suppressor that acts through the direct regulation of p53 in human lung cancer [73,74].…”
Section: Sox Protein Familymentioning
confidence: 99%